Establishing the Basis for Mechanobiology-Based Physical Therapy Protocols to Potentiate Cellular Healing and Tissue Regeneration - Ng, Joanna L.; Kersh, Mariana E.; Kilbreath, Sharon; Knothe Tate, M. (Frontiers in Physiology, 2017)
Life is mechanobiological: mechanical stimuli play a pivotal role in the formation of structurally and functionally appropriate body templates through mechanobiologically-driven cellular and tissue re/modeling. The body responds to mechanical stimuli engendered through physical movement in an integrated fashion, internalizing and transferring forces from organ, through tissue and cellular length scales. In the context of rehabilitation and therapeutic outcomes, such mechanical stimuli are referred to as mechanotherapy. Physical therapists use mechanotherapy and mechanical interventions, e.g. exercise therapy and manual mobilizations, to restore function and treat disease and/or injury. While the effect of directed movement, such as in physical therapy, is well documented at the length of the body and its organs, a number of recent studies implicate its integral effect in modulating cellular behavior and subsequent tissue adaptation. Yet the link between movement biomechanics, physical therapy and subsequent cellular and tissue mechanoadaptation is not well established in the literature. Here we review mechanoadaptation in the context of physical therapy, from organ to cell transduction and cell to organ scale extracellular matrix genesis and re/modeling. We suggest that physical therapy can be developed to harness the mechanosensitivity of cells and tissues, enabling prescriptive definition of physical and mechanical interventions to enhance tissue genesis, healing and rehabilitation.